(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2026)
This article examines the theoretical foundations and practical approaches to developing creativity qualities in university students. The study analyses the conditions necessary for establishing a creative educational environment and identifies the key personal qualities characteristic of creative thinkers. Drawing on the works of Patti Drapeau and other leading researchers in the field, the article presents four evidence-based ways to cultivate creative thinking skills: forming creative thinking skills through the use of action-oriented verbs, developing practical creative skills through interactive methods, organizing creative activity processes, and applying creative products as learning outcomes. Special attention is given to the neurological basis of creative thinking, the role of the teacher in fostering a psychologically safe and stimulating classroom environment, and the importance of collaborative group work. The article also discusses the factors that hinder the development of creativity and proposes practical recommendations for integrating creative approaches into higher education pedagogy. The findings suggest that creative thinking can be developed as a sustainable habit when appropriate pedagogical conditions are systematically created and maintained.